Metropolitan Museum of Art - Collection - NC (NC, 2026)
Collection en ligne du Met, avec œuvres du monde entier, notices, images et informations de conservation.
This work is licensed under a Creative Commons Attribution-NonCommercial 4.0...
Keywords: Met; art; collections; museum